(untitled) (Perner’s Contacts, 2019)
Inland water transport has clearly bent on the use of dual-fuel systems diesel - LNG. The wider use of this fuel in transport is preceded by the need to create a functioning market with the closest connection to solving many logistical problems not only within the region but also in terms of production regions as well as the physical properties of LNG related to its long-range transport. The current legislation on the transport of dangerous goods (ADN) allows the use of LNG tankers equipped with special containers - cryogenic storage tanks for the transport of LNG by inland waterways. Similar tanks can also be used for long-term storage at central terminals. Although this technology is not new, its application to inland vessels is on very low level. When constructing and placing tanks on existing vessels, it is necessary to seek compromises taking into account both the shape of the tank and the amount of stored gas, as well as the insulation and strength characteristics.